Henry Wadsworth Longfellow papers - Longfellow, Henry Wadsworth, 1807-1882.
Letters, poems and drafts of poems, clippings, photograph, and other items. Includes working draft with corrections (1842) of Longfellow's poem, "The Village Blacksmith." Also includes an undated account written by Longfellow of a discussion with Nathaniel Hawthorne of the idea for Longfellow's poem, "Evangeline."
In part, positive photocopy, handwritten and typewritten transcripts, and facsimiles.
Poet.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Hawthorne, Nathaniel, -- 1804-1864.; American poetry -- 19th century; Poets